Polydatin nanoparticles attenuate oxidative stress and histopathological changes in streptozotocin model of diabetic nephropathy: targeting Nrf2/HO-1/NF-κβ signaling pathways - Manal Abdul-Hamid; Sanaa R. Galaly; Hanaa M. Mohamed; Fatma Mostafa; Adel Abdel-Moneim (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background One of the most prevalent and serious side effects of diabetes mellitus is diabetic nephropathy, which is characterized by abnormalities in kidney structure that can occur before kidney function declines. Up to 90% of persons with diabetic nephropathy and 40% of adults with severe diabetic nephropathy are unaware that they have kidney disease. Through Nrf2/HO-1/NF κβ/TNF α signaling pathways, biochemical, oxidative stress, and antioxidant biomarkers, ultrastructural, immunohistochemical, and histopathological studies, so we attempt to evaluate the potential corrective mechanisms of polydatin nanoparticles against diabetic nephropathy in comparison with polydatin and metformin. Results POLY-CSNPs, POLY, and METF treatment lowered fasting superoxide dismutase, catalase activities, and glutathione content in treating the diabetic blood sugar level, glycosylated hemoglobin percentage, and oxidative stress such as lipid peroxidation level, and also enhanced antioxidant biomarkers like superoxide peroxidase, superoxide dismutase, catalase activities, and glutathione content in treating the diabetic nephropathy. POLY-CSNPs, POLY, and METF also significantly reduced the area % of immunohistochemical reaction of TNF α (tumor necrosis factor alpha) and NF κβ (nuclear factor-kappa-β), while significantly increasing the mRNA expression’s levels for nuclear factor erythroid 2-related factor 2 and heme oxygenase-1. The results observed that POLY-CSNPs showed extremely significant efficacy in treated diabetic rats as contrasted with POLY. Histological and ultrastructural studies showed marked improvement in glomeruli, basal laminae, and proximal tubules appearing nearly identical to the normal. Conclusions POLY-CSNPs revealed a marked ameliorative effect on diabetic nephropathy via its anti-inflammatory, antioxidant, and prolonged-release properties.